Digital Leadership Enhances Employee Empowerment, Techno-work Engagement, and Sustainability: SEM Analysis in Public Healthcare - Ali Nawaz Khan PhD; Yumei Wang MN; Naseer Abbas Khan PhD; Ali Ahmad PhD (Inquiry: The Journal of Health Care Organization, Provision, and Financing)
The rapid digital transformation in the public healthcare sector demands effective digital leadership to improve organizational performance. This study investigates the impact of digital leadership on employee empowerment and its subsequent effects on techno-work engagement and sustainability performance within public healthcare institutions in Pakistan. A survey-cum questionnaire method was employed for 334 respondents of employees of public healthcare institutions in the Punjab Province of Pakistan. It used structured questionnaires to measure digital leadership, sense of empowerment, techno-work engagement, and sustainability performance. Structural Equation Modeling (SEM) was performed on data to examine the proposed relationships among the variables. The findings of SEM showed that digital leadership positively influences employees’ sense of empowerment. Empowerment significantly predicted techno-work engagement and sustainability performance. Techno-work engagement also positively affected sustainability performance. Mediation analysis revealed that the sense of empowerment mediates the relationship between digital leadership and both techno-work engagement and sustainability performance. The findings demonstrate that digital leadership enhances employee empowerment, which in turn boosts techno-work engagement and sustainability performance in the public healthcare sector. Organizations should promote digital leadership practices to empower employees and achieve sustainable outcomes.